Pattern Recognition Receptors in HIV Transmission - Geijtenbeek, Teunis B.; Mesman, Annelies (Frontiers in Immunology, 2012)
Dendritic cells (DCs), Langerhans cells (LCs) and macrophages are innate immune cells that reside in genital and intestinal mucosal tissues susceptible to HIV-1 infection. These innate cells play distinct roles in initiation of HIV-1 infection and induction of anti-viral immunity. DCs are potent migratory cells that capture HIV-1 and transfer virus to CD4+ T cells in the lymph nodes, whereas LCs have a protective anti-viral function, and macrophages function as viral reservoirs since they produce viruses over prolonged times. These differences are due to the different immune functions of these cells partly dependent on the expression of specific pattern recognition receptors. Expression of Toll-like receptors, C-type lectin receptors and cell-specific machinery for antigen uptake and processing strongly influence the outcome of virus interactions.